Study of quinoa, Chenopodium quinoa Willd, as an alternative natural fertilizer by nuclear analytical methods - Soto, R. L. (2015)
On the base of the application of multielemental analytic methods of characterization of organic samples, such as the fluorescence of X-rays, neutron activation analysis and Coleman chemical analysis, the possibility of use of several parts of the plant named Quinua, Chenopodium quinoa Willd is suggested as alternative natural fertilizer for this crop.